Gender Discrimination in Mahesh Dattani‟s Play Thirty Days in Septembe - Kalaiselvi, R. (International Journal of Psychosocial Rehabilitation, 2020)
This paper attempts to analysethe gender discrimination in Mahesh Dattani’s Thirty Days in September. This paper discuses about the discrimination, women face when she is in relationship or the discrimination which she faces at home, society and the problems the women face on gender or sex. Gender inequality refers that men are superior to women or women are superior to men. Whenever a gender is dominated in the society, it is termed as gender inequality. Gender discrimination occurs in homes, colleges, workplaces, parks and other public places. Women folk as mother, wife, daughter, take care of children in these roles of women in Indian Society. The role of women in India is in low esteem and their economic condition is dependent. So women are considered as the weaker sex of the society. Mahesh Dattani is one of India’s most daring and innovative playwrights writing in English today. In the world of Indian English theatre, Mahesh Dattani is a name for the fusion of an actor, director, a social thinker and “new avante-garde”. Dattani, the young Indian playwright, the winner of prestigious Sahitya Akadami Award for Dramaturgy, was born on 7th of August 1958 in Gujarat. Mahesh Dattani’s plays discuss too many challenges faced by women like poverty among women, unequal job opportunities, women’s empowerment, family, wages, education, religion, child abuse, political power etc. This paper will discuss gender discrimination as found in Mahesh Dattani’s work and suggests answers to questions of dealing with the problem of gender discrimination. The Protagonists of this play suffer by the gender discrimination in different ways.